1980
DOI: 10.1080/00288233.1980.10425362
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus uptake and return in grazed, steep hill pastures

Abstract: Ministry 01' Agriculture and Fisheries, P.ß., Hamilton, New Zealand Pasture production and dung and Iitter accumulation weremeasured on a range 01' slopes on both a north-facing and a south-facing steep hili paddock for I year. All parameters decreased in the following order: campsites, 2SO slopes, 4SO slopes. Pasture production and dung accumulation declined sharply with increase in surface slope. In particular dung accumulation ranged from very high on campsites to negligible on 45°slopes. The accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, dung P is the prevalent pathway for animal returns to grazed pastures (Haynes and Williams 1993). This is far from being evenly distributed on the landscape (Bilotto et al, 2019); rather, it is returned in small areas at high concentrations (Gillingham, 1980). The concentration of P in dung from grazing ruminants is often much greater than in the herbage consumed, and has been reported to be up to a four-fold greater (Shand and Coutts 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dung P is the prevalent pathway for animal returns to grazed pastures (Haynes and Williams 1993). This is far from being evenly distributed on the landscape (Bilotto et al, 2019); rather, it is returned in small areas at high concentrations (Gillingham, 1980). The concentration of P in dung from grazing ruminants is often much greater than in the herbage consumed, and has been reported to be up to a four-fold greater (Shand and Coutts 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that percentages of the different earthworm species were influenced by grazing management but not by slope of sample site. Flatter sites have much higher dung inputs (Gillingham 1980) and treading pressure (Rumball 1966) than steeper sites, conditions under which the dung-consuming L. rubellus might be expected to be relatively more numerous. Sears and Evans (1953) remarked that liveweight of earthworms below, and of sheep above, a pasture would be similar, however this was not the case at Ballantrae.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly E. coli risk was greatest in sheep dung than dairy cattle or deer dung. For all other contaminants, risk was greater for dairy cattle dung than deer or sheep (Gillingham et al, 1980;Rowarth et al, 1988). For instance, Gillingham et al (1980) found that TP in sheep dung was least in summer and autumn (7.3-8.2 g kg −1 ) and greatest in spring (14.6 g kg −1 ), while winter was intermediate (10.5 g kg −1 ).…”
Section: Perspectivementioning
confidence: 95%
“…For all other contaminants, risk was greater for dairy cattle dung than deer or sheep (Gillingham et al, 1980;Rowarth et al, 1988). For instance, Gillingham et al (1980) found that TP in sheep dung was least in summer and autumn (7.3-8.2 g kg −1 ) and greatest in spring (14.6 g kg −1 ), while winter was intermediate (10.5 g kg −1 ). Concentrations of N in dung remain fairly constant at about 1% of N in feed (Barrow and Lambourne, 1962), while excess N is excreted in urine, which can account for 80% of N deposited by an animal (Ledgard et al, 1998).…”
Section: Perspectivementioning
confidence: 95%